توصيف بعض طرز الباذنجان solanum melongena L. تحت ظروف الزراعة المحلية (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
Morphological characterization is the first stage of the identification and classification of genetic resources. In this study, the aim was to determine the similarities and differences in the morphological variations of the eggplant Type collected from different eco-geographical regions of syria. The experiment was arranged in Complete  Randomized Block Design with 4 replications. 12 types of eggplant were characterized using standard morphological descriptors specified by the IBPGR. T4 recorded significantly higher number of fruits (14.235) followed by T3 (12.303) and T2 (10.423). Fruit length was maximum in T6 (12.51 cm) followed by T1 (12.23 cm).  plant height was maximum in T3 (160.2cm) followed by T5 (140.5 cm).T4 took the maximum fruit yield per plant (1.998kg), while minimum value for fruit yield per plant were observed in T10 (0.920 kg). يعتبر التوصيف المورفولوجي الخطوة الأولى لتعريف وتصنيف المصادر الوراثية, لذلك هدفت هذه الدراسة لتحديد التشابهات والاختلافات في الأنماط الشكلية للباذنجان التي جمعت من مناطق جغرافية وبيئية مختلفة في سوريا, حيث نفذت التجربة وفق تصميم القطاعات العشوائية الكاملة بـ 4 مكررات، ووصف 12 طراز من الباذنجان بالاعتماد على معايير التوصيف الشكلي الموضوعة من قبل IBGRI. سجل الطراز T4 أعلى متوسط لعدد الثمار على النبات الواحد (14.235) تلاه  T3(12.303) و T2 (10.423), وكان أعظم متوسط طول للثمرة للطراز T6 (12.51) سم تلاه T1 (12.23)سم, في حين كان متوسط أعلى ارتفاع للنبات للطراز T3 ((160.2 سم تلاه T5(140.5) سم, سجل T4 أكبر متوسط إنتاجية للنبات الواحد (1.998)كغ بينما أدنى قيمة لمتوسط إنتاجية النبات الواحد لوحظت عند الطراز T10 (0.920) كغ.